ASSESSMENT OF SOIL AND WATER QUALITY AND ITS POSSIBLE IMPACT ON THE FLORA AND FAUNA IN JAYARAMPETTAI VILLAGE OF RANIPET DISTRICT, TAMIL NADU, INDIA - ARIVOLI, SUBRAMANIAN; TENNYSON, SAMUEL; MANIMEGALAI, GANESAN; VIGNESHKUMAR, ELANGOVAN; MEERAN, MOHAMED; MARIN, GRACE; VASSOU, MIRIAM; DIVYA, SELVARAJ; KAMATCHI, PAC (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The quality of soil and water from Jayarampettai village of Ranipet district, Tamil Nadu, India were tested from January 2019 to December 2019, and checked for its impact on the flora and fauna. The physicochemical, macronutrient and metal parameters for soil tested in the study area reported higher concentrations of iron and manganese which act as important indicators for environmental risk assessment creating awareness towards safe guarding of flora and fauna biodiversity. However, the metal parameters during water analysis were nil. The soil quality in polluted condition due to industrialization will certainly cause harm to the growth and quality of plant and animal life. Future studies on soil and water analysis of other villages in Ranipet district would determine the quality of soil and water for biotic community.